A Direct Observation of Infanticide by a Female Free-Ranging Dog (Canis familiaris) Supports the Resource Competition Hypothesis - Vanderheyden, Melissa; Chaignon, Brenda; Car, Clément; Pilot, Małgorzata; el Berbri, Ikhlass; Marshall-Pescini, Sarah; Range, Friederike; Berghänel, Andreas (Ecology and Evolution, 2025)
Infanticide by females occurs in many mammalian species but is rarely observed directly, making its social and ecological determinants difficult to identify. Here, we report the first direct observation of within-pack infanticide by a female free-ranging domestic dog. To assess whether this case can be better explained by resource competition or nutritional gain, we examined the social context in which it occurred. In our long-term study population, we identified 26 cases characterised by a similar pattern of overlapping pregnancies within social groups. By comparing dominance rank and birth order across cases, we found that subordinate females time their births after or in synchrony with the alpha female, which may be a strategy to reduce infanticide risk. By giving birth later, the subordinate potentially allows the alpha a competitive advantage, thereby reducing the incentive for infanticide. Furthermore, subordinate free-ranging dogs may use communal denning as a protective measure, as it hinders the identification of individual litters. In our study, the infanticide followed a period of rank instability. Social rank instability could elevate infanticide risk, since the absence of dominance signals might complicate the subordinate's assessment of the potential threat to its offspring, or because infanticide is used to consolidate dominance. On the other hand, we did not find support for the hypothesis that insufficient nutrition motivated the infanticide, based on an evaluation of the body condition scores within the pack and on the observation that not all killed pups were eaten. Taken together, our preliminary findings suggest that resource competition rather than nutritional gain may better explain infanticide by female free-ranging dogs.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Canidae; communal breeding; reproductive conflict; reproductive suppression; reproductive synchrony; threat of infanticide